2019
DOI: 10.1177/1043986219870941
|View full text |Cite
|
Sign up to set email alerts
|

Victimization, Crime Propensity, and Deviance: A Multinational Test of General Strain Theory

Abstract: General Strain Theory (GST) identifies victimization as one of the strains most strongly related to crime which, like other sources of strain, is moderated by individual and social factors. Recently, Agnew extended the theorization of coping strategies by proposing that the effects of strain on deviance are conditioned by individual and social factors in combination, rather than singly, which he labeled crime propensity. Tests of the propensity hypothesis have so far yielded mixed results, highlighting the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
(94 reference statements)
0
5
0
1
Order By: Relevance
“…Crime or deviance is a possible way to cope with strain and related emotions. GST researchers have treated victimization as a typical facet of exposure to negative stimuli that results in crime/delinquency (Barbieri et al, 2019; Teijón-Alcalá & Birkbeck, 2019). Alternatively, GST can inform a pathway that connects crime/delinquency to victimization.…”
Section: Theoretical Precepts That Assume the Victim-offender Overlapmentioning
confidence: 99%
See 1 more Smart Citation
“…Crime or deviance is a possible way to cope with strain and related emotions. GST researchers have treated victimization as a typical facet of exposure to negative stimuli that results in crime/delinquency (Barbieri et al, 2019; Teijón-Alcalá & Birkbeck, 2019). Alternatively, GST can inform a pathway that connects crime/delinquency to victimization.…”
Section: Theoretical Precepts That Assume the Victim-offender Overlapmentioning
confidence: 99%
“…Differential association/learning theory holds that deviance is acquired in the course of interaction with deviant others via the learning of their motives and techniques (Sutherland & Cressey, 1978). Schreck et al (2008) once opined that this theory is geared toward explicating offending instead of victimization, because the idea of learning vulnerability to victimization does not make sense.…”
Section: Differential Association Theorymentioning
confidence: 99%
“…Otherwise, they may themselves become a predator and seek suitable targets to alleviate their negative emotions through perpetrating the same behaviors by which they were victimized. Drawing on the GST framework, some empirical studies have examined the effects of victimization on criminal coping and found a significant relationship between them (Baron, 2004; Craig et al, 2017; Hay & Evans, 2006; Moon & Morash, 2017; Ostrowsky & Messner, 2005; Teijón-Alcalá & Birkbeck, 2019).…”
Section: Victimization As a Criminogenic Strain And Bullying Perpetra...mentioning
confidence: 99%
“…The loss of positive stimuli refers to the removal of a positively valued resource, such as a family member. The third, the presentation of negative stimuli, refers to the addition of a negative event or influence, such as delinquent peers (Agnew, 1985;Ford, 2014;Teijón-Alcalá & Birkbeck, 2019). In the current study, the primary focus is on the first type of strain, as we are focusing on the influence of socioeconomic strains.…”
Section: Female Offending and Strainmentioning
confidence: 99%